2017
DOI: 10.3892/etm.2017.4029
|View full text |Cite
|
Sign up to set email alerts
|

Image-guided minimally invasive percutaneous treatment of spinal metastasis

Abstract: Abstract. In order to provide effective options for minimally invasive treatment of spinal metastases, the present study retrospectively evaluated the efficacy and safety of image-guided minimally invasive percutaneous treatment of spinal metastases. Image-guided percutaneous vertebral body enhancement, radiofrequency ablation (RFA) and tumor debulking combined with other methods to strengthen the vertebrae were applied dependent on the indications. Percutaneous vertebroplasty (PVP) was used when vertebral bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Following the review of abstracts and titles, 63 full-text articles were ordered for assessment. On full paper review, 8 non-randomised studies (3 prospective case series, 1 prospective interventional study and 4 retrospective case series) that investigated RFA alone or in combination with another treatment were identified and included for the final analysis [8,10,[14][15][16][17][18][19]. No randomised controlled trials met the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following the review of abstracts and titles, 63 full-text articles were ordered for assessment. On full paper review, 8 non-randomised studies (3 prospective case series, 1 prospective interventional study and 4 retrospective case series) that investigated RFA alone or in combination with another treatment were identified and included for the final analysis [8,10,[14][15][16][17][18][19]. No randomised controlled trials met the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…In the series by Nakatsuka et al [14], 1 out of 10 patients reported a grade II complication consistent with a transient neural damage related to the high temperature raise during RFA; such complication completely resolved 2 days after the procedure with intravenous administration of steroids. On the other hand, Yang et al [18] reported side effects related to RFA in 4 out of 25 patients (16%). Of these, two experienced contralateral lower limb pain and numbness during the procedure; however, such symptomatology spontaneously disappeared with temperature decrease after RFA (grade I complication).…”
Section: Safetymentioning
confidence: 97%
See 2 more Smart Citations
“…Minimally invasive percutaneous image-guided techniques for the treatment of spine tumors include newer technologies, such as radiofrequency ablation (RFA) [34], cryoablation, microwave ablation, alcohol ablation, and laser photocoagulation. These modalities provide an alternative or adjunct therapeutic option for the treatment of spinal tumors beyond medical pain management, surgery, radiation therapy (RT), and standard VA. Curative ablation can be applied for the treatment of specific benign or in selected cases of malignant localized spinal tumors.…”
Section: Special Treatment Considerationsmentioning
confidence: 99%